(untitled) (Research, Society and Development, 2022)
This research aims to investigate whether the objectives of the educator training course for the use of the LEGO Braille Bricks (LBB) kit as a pedagogical resource for the development of pedagogical activities with students aged 4 to 10 years were achieved, according to the perception of the participating course educators. The theoretical foundation is based on the main Brazilian legislation on inclusion, on the concept of Proximal Development Zone (ZPD) (Vygotsky, 2009), and the Constructionist, Contextualized and Meaningful (CCS) approach (Schlünzen, 2000, 2015; Schlünzen et al., 2020). The participants were 16 educators belonging to four institutions that support people with Visual Impairment (VI) in the state of São Paulo, Brazil, and two tutors. The methodological approach consisted in the analysis of data from the records available in the Virtual Learning Environment (VLE), and a questionnaire applied to the participating educators at the end of the training course. The results indicated that the pedagogical mediation enabled course educators to establish a collaborative network between all the included institutions in order to share strategies in remote teaching of people with VI. In addition, the activities developed demonstrated that everyone was able to make use of LBB to assist their students with VI and favor the literacy process.